The simulation model of IT-product (service) development by a "start-up" company growing inside an academic institution - Lytvynov, V.V.; Saveliev, M.V. (Математичні машини і системи, 2015)
The simulation model of IT-product or service development by a "start-up" company growing inside an academic institution's "business center" is reviewed. The purpose of the model is to estimate final dates of reaching project goals of the "start-up" company. The use of Petri nets for design of such model is shown. An example of model implementation by means of agent simulation is given.